Portfolio Mapping, Innovation Potential and Strengthening Agricultural Entrepreneurship - Yoesdiarti, Arti (JURNAL AGRIBISAINS, 2023)
Rural areas have abundant potential natural resources, especially in agriculture, which can be developed to strengthen the welfare of the community. The research aims to identify village conditions and business portfolios, analyze possible innovations and adoptions to improve agricultural performance, analyze factors that can strengthen innovation, and analyze processes to strengthen adoption and innovation. The research was conducted in Cipayung Village, Megamendung District, Bogor Regency in May - June 2023. The analysis was carried out through in-depth interviews with 6 (six) representatives of parties involved in the agricultural development process in Cipayung Village, namely farmer group leaders, MSME actors, village extension workers, village secretary, youth group head, and West Java P4S Chair. The data is processed qualitatively. The results of the study indicate that the condition of resources in Cipayung Village can be developed, the business portfolio also supports the existence of a collaborative process for agricultural development. Identification of innovation and adoption indicates that there are opportunities for innovation development in terms of products, processes, marketing, organizations and markets. Innovation is devoted to producing high-quality, unique, and highly potential market products in order to gain a higher profit, considering the limited land due to land conversion. Factors that can strengthen innovation are strengthening human resources, social resources, capital resources, and infrastructure. This research is expected to strengthen agricultural performance and encourage the youth to be part of the agriculture development program in Cipayung Village.